Cestode Infection in the Digestive Tract of Ducks from Chicken Slaughterhouses in Bojong Gede and Cibinong Market, Bogor, West Java - Aviola, Lala; Tiuria, Risa; Nugraha, Arifin Budiman (Jurnal Medik Veteriner, 2022)
Helminthiasis is a crucial gastrointestinal endoparasitic in ducks. This study aimed to determine the type and degree of infection of adult worms in the digestive tract of ducks at a chicken slaughterhouse in Bogor Regency, West Java. A total of 10 samples of the digestive tract of ducks were collected in this study. Five ducks were collected from a chicken slaughterhouse in Bojong Gede District and five other ducks were collected from a market in Cibinong City. Each intestinal sample was divided into 4 parts, i.e. the duodenum, jejunum, ileum and cecum. Adult cestode worms were stained with Semichon's Acetocarmine for identification. In result, three ducks were positive for endoparasite infection. The cestodes found were Raillietina cesticillus with 20% degree of infection in the jenjunum and ileum respectively. Hymenolepis nana with 20% degree of infection in the jejunum and ileum respectively. Choanotaenia infundibulum with 10% degree of infection in the ileum.